2017
DOI: 10.1021/acs.chemmater.7b00376
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Bulk Boron-Doped Graphitic Carbon

Abstract: The single-step reaction of benzene and boron tribromide in a closed reactor at elevated temperature (800 °C) results in the synthesis of bulk boron-doped graphitic carbon. Materials of continuously tunable composition BC x ′ are accessible (x ≥ 3), exhibiting the structure of a solid-solution of boron within turbostratic graphite (G′). Upon extended heat treatment or at higher temperatures, graphitic BC x ′ is leached of boron and undergoes a phase separation into boron carbide and graphite. Higher boron cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…Boron doping is an efficient route to lower the Fermi level of carbon by introducing electron deficiency into the carbon structure and forming a p ‐doped semiconductor, which leads to increased capacity of intercalated sodium ions . In addition, the B‐doped carbon can still keep the planar structure of carbon without obvious structure deformation.…”
Section: Synthesis and Electrochemical Performance Of Heteroatom‐dopementioning
confidence: 99%
See 1 more Smart Citation
“…Boron doping is an efficient route to lower the Fermi level of carbon by introducing electron deficiency into the carbon structure and forming a p ‐doped semiconductor, which leads to increased capacity of intercalated sodium ions . In addition, the B‐doped carbon can still keep the planar structure of carbon without obvious structure deformation.…”
Section: Synthesis and Electrochemical Performance Of Heteroatom‐dopementioning
confidence: 99%
“…The obtained B‐OLC contained 5.52 at% boron and showed an obvious graphite ring (002), indicating the conversion of nanodiamond into the sp 2 carbon phase. Kovalenko and co‐workers synthesized a bulk B‐doped graphitic carbon through a one‐step thermal method with liquid boron tribromide and benzene as precursors . The obtained B‐doped graphitic carbon shows a flake‐like morphology with dark metallic luster.…”
Section: Synthesis and Electrochemical Performance Of Heteroatom‐dopementioning
confidence: 99%
“…There have been few experimental reports focused on the electrochemical performance of boron‐doped carbon materials. Stadie et al showed that B‐doped amorphous carbon synthesized by a reaction between benzene and boron tribromide in a closed reactor at an elevated temperature, delivered a reversible capacity around 278 mAh g −1 at 0.1 A g −1 , as shown in Figure g,h. It is a pity that the electrochemical performance of the undoped carbon was not provided.…”
Section: Heteroatom Doping To Obtain a Higher Reactivitymentioning
confidence: 98%
“…h) Galvanostatic discharge–charge profiles of a boron‐doped carbon electrode at a current density of 0.1 A g −1 . g,h) Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Heteroatom Doping To Obtain a Higher Reactivitymentioning
confidence: 99%
“…There is a particular interest in boron doped graphite, as previous experimental results suggest that boron can be doped into graphite at a wide range of concentrations and that such doping leads to an increase in lithium intercalation voltage, in agreement with our calculation and theory. [18][19][20][21][22][23][24][25][26][27][28][29] For example, experiments have shown that boron can be doped into graphite from low concentrations around 0-3 at% 18,23,28 to very high concentration of 25-50 at% without loss of the graphite structure. 19,21,29 In the case of very high concentrations, Stadie et al 21 showed that the boron concentration in direct synthesis can be continuously varied up until 25 at% without the formation of carbide and that boron doping is accompanied by increased capacity/voltage.…”
mentioning
confidence: 99%